A case-control study on depression, anxiety, and belief in sexual myths in trans women - Uyar, Betul; Yucel, Ilyas; Uyar, Emre; Ateş Budak, Elif; Kelle, Ilker; Bulbuloglu, Semra (Frontiers in Psychiatry, 2023)
Objective The purpose of our study was to investigate depression, anxiety, and belief in sexual myths in trans women. Methods This is a prospective case-control study. The case group included 60 trans women who were referred to the Medical Biology and Genetics Department from various clinics of the research and training hospital where this study was conducted. The control group consisted of 60 healthy male individuals who presented to the same hospital for routine health follow-ups and collecting documents showing their health. In data collection, we used a Personal Information Form, the Sexual Myths Scale, and the Beck Depression and Anxiety Inventories. The IBM Statistical Package for the Social Sciences 25.0 was used to analyze the data. Results In the case group, 26.7% of the participants were sex workers, and all were single. While 46.7% of the participants in the case group were living with their families, 66.7% were smokers, and 13.3% were receiving hormone treatment. All 60 participants in the control group were also single. The participants in the control group had higher levels of believing sexual myths and lower levels of anxiety and depression than those in the case group (p = 0.000). The mean scores of the participants in the control group in the Sexual Orientation and Sexual Violence subscales of the Sexual Myths Scale were higher than the mean scores of those in the case group (p < 0.05). Conclusion The trans women who participated in this study had higher levels of anxiety and depression and lower levels of believing sexual myths than the control group. The mental health of trans women can be disrupted due to various treatments they are exposed to in society such as stigma, discrimination, and violence. Their higher anxiety and depression levels in this study could be explained by this exposure. This exposure could also have led to their lower total scores in the Sexual Myths Scale, as well as lower scores in the Sexual Violence and Sexual Orientation subscales.